A commentary on Isocrates' Busiris - Livingstone, Niall (Brill, 2001)
This volume contains the first scholarly commentary on the puzzling work Busiris - part mythological jeu d'esprit , part rhetorical treatise and part self-promoting polemic - by the Greek educator and rhetorician Isocrates (436-338 BC). The commentary reveals Isocrates' strategies in advertising his own political rhetoric as a middle way between amoral 'sophistic' education and the abstruse studies of Plato's Academy. Introductory chapters situate Busiris within the lively intellectual marketplace of 4th-century Athens, showing how the work parodies Plato's Republic , and how its revisionist treatment of the monster-king Busiris reflects Athenian fascination with the 'alien wisdom' of Egypt. As a whole, the book casts new light both on Isocrates himself, revealed as an agile and witty polemicist, and on the struggle between rhetoric and philosophy from which Hellenism and modern humanities were born.
10.1163/9789047400929